GAMBARAN TINGKAT PENGETAHUAN DAN KEPATUHAN IBU HAMIL TENTANG KONSUMSI Tablet Fe DENGAN APLIKASI POIN OTDA DI PUSKESMAS ALALAK SELATAN - Amaliyah Wahyuni; Ahmad Maki Zamzami (Jurnal Insan Farmasi Indonesia, 2020)
Smartphones seem to be a mandatory item for humans in searching for information, including pregnant women can easily found a health information. Knowledge of the importance of nutritional needs during pregnancy is very influential on maternal and infant health, during pregnancy, nutritional consumption needs increase rapidly, especially consumption of iron. Iron deficiency during pregnancy can cause babies born to be at risk for Stunting. Good knowledge and adherence can minimize the risk of maternal and child. The purpose of this study was to determine the level of knowledge and adherence of pregnant women about Fe consumption with the application of OTDA points. The next objective was to find out whether there was a difference between the knowledge before and after giving the application of OTDA points. The study population was pregnant women who had their pregnancies examined at the South Alalak Health Center. Respondents used in this study were 266 people. The level of knowledge of respondents before giving the OTDA application was sufficient (61.61%) and after giving the application increased to a good category (72.66%). While the level of compliance with the use of iron Fe was measured when the non-compliant post-test was 66% and the obedient was 34%